ANALISIS HIGIENE SANITASI DEPOT AIR MINUM ISI ULANG (DAMIU) DI SEKITAR UNIVERSITAS ISLAM RIAU - Mairizki, Fitri (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2017)
The existence of Drinking Water Refill Depot (DAMIU) continues to increase appropriate with the dynamics of community needs for drinking water that has good quality and safe for consumption. Although it had a low price, not all DAMIU product guaranteed safety. DAMIU as an alternative choice to fulfill the community needs for drinking water becomes a risk that harmful to health if consumers did not pay attention in DAMIU hygiene and sanitation. Therefore, the purpose of this study was to analyze hygiene and sanitation of DAMIU building, equipment and operator. The type of this research was descriptive research.The data obtained in this study was primary data in the form of observation using checklist sheet. The data was presented in tabular form and discussed descriptively. In general, hygiene and sanitation of DAMIU building and equipment were good but the sanitation facilities still minimals, the wash basin for operators and its tools were not available. There were several of operators hygiene must be considered. All operators did not using special uniform for work, did not conducting periodic medical examinations and did not have sertificate of hygiene sanitation course.